2011
DOI: 10.1007/s10664-011-9195-3
|View full text |Cite
|
Sign up to set email alerts
|

Clones: what is that smell?

Abstract: Clones are generally considered bad programming practice in software engineering folklore. They are identified as a bad smell (Fowler et al. 1999) and a major contributor to project maintenance difficulties. Clones inherently cause code bloat, thus increasing project size and maintenance costs. In this work, we try to validate the conventional wisdom empirically to see whether cloning makes code more defect prone. This paper analyses the relationship between cloning and defect proneness. For the four medium to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(45 citation statements)
references
References 40 publications
0
44
0
1
Order By: Relevance
“…Researchers have presented evidence that code clones have both positive [14], [25] and negative [18] consequences for maintenance activities and thus, in general, code clones are neither good nor bad. It is also not possible or practical to eliminate certain clone classes from a software system to minimize their potential threats [14].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have presented evidence that code clones have both positive [14], [25] and negative [18] consequences for maintenance activities and thus, in general, code clones are neither good nor bad. It is also not possible or practical to eliminate certain clone classes from a software system to minimize their potential threats [14].…”
Section: Introductionmentioning
confidence: 99%
“…Decision tree has been used to predict developers' contribution in [145]. In [65], SVM has been applied for the bug triage and in [147], association rule mining has refactoring [72], [73] API-change [74], [75], [77], [80], [81] change patterns [83]- [88], [90], [160] team-activity developer's contribution [55], [91], [93], [94], [154] experties of developers [96], [97], [149] tool support [98], [99], [128], [151] helpful information [100] comprehension visualization [101], [102], [156] identifiers [104], [105], [153] recording operations [106] validation metrics [45], [107], [157] tool [108] clones [109]- [112], [150], [159] bug [113], [114] development& evolution development [118]- [120] evolution …”
Section: Data Mining Algorithmsmentioning
confidence: 99%
“…However, they could not find systematic relation between them [159]. Rahman et al empirically validated the general negative characteristics of clones [112]. The relations between clones and defect-proneness have been analyzed, and they concluded that most of bugs are not seriously related to clones, clones are less defect-prone than non-cloned codes.…”
Section: To Empirically Validate Novel Ideas and Techniquesmentioning
confidence: 99%
“…It always produces an adverse effect on the system. When anti-pattern occurs in a software system, it is detected by the code smells (Rahman et al, 2012). Code smell is not Antipattern at the deign level, but it can be at the programming level (Carneiro et al, 2010).…”
Section: Introductionmentioning
confidence: 99%